E-Service Quality And E-Trust Toward Online Shop Customers E-Loyalty: Satisfaction as Mediation - Sihombing, Nikous Soter; Simbolon, Sahat; Susanto, Agus; Tarigan, Sri Aprianti (Univeristas Islam Bandung, 2023)
The purpose of this study is to analyze the relationship between the effect of e-service quality on e-satisfaction, the effect of e-trust on e-satisfaction, the effect of e-service quality on e-customer loyalty, the effect of e-service quality on e-customer loyalty, the effect of e- satisfaction on e-customer loyalty, indirect effect of e-service quality on e-customer loyalty through e-satisfaction, significant indirect effect of e-trust on e-customer loyalty through e-satisfaction. The research method is quantitative, the technique sampling used using purposive sampling method category of non-probability sampling. Respondents to this study were 310 online shop consumers who had purchased goods/services at the online shop. Research data was obtained by distributing online questionnaires via social media. Analysis of research data using structural equation modeling (SEM) with SmsrtPLS 4.0 software tools. The stages of data testing are validity test, reliability test and hypothesis testing (significance). The results of this study are that there is a direct positive and significant effect of e-service quality on e-satisfaction. There is a direct positive and significant effect of e-Trust on e-Satisfaction There is a direct positive and significant effect of e-service quality on e-Customer Loyalty, there is a strong positive and significant direct effect of e-Trust on e-Customer Loyalty, there is a positive effect and directly significant e-Satisfaction on e-Customer Loyalty, there is a strong and significant positive effect indirectly e-service quality on e-Customer Loyalty through e-Satisfaction, there is a strong and significant positive effect indirectly e-Trust on e-customers loyalty through e-Satisfaction.